Transitions in the German labor market: Structure and crisis - Michael U. Krause; Harald Uhlig (Deutsche Bundesbank, 2011)
Since the so-called Hartz IV reforms around 2005 and during the global crisis of 2008/2009, the German labor market featured mainly declining unemployment rates. We develop a search and matching model with heterogeneous skills to explore the role of structural and cyclical policies for this performance. Calibrating unemployment benefits to approximate legislation before and after the reforms, we find a large reduction in unemployment and its duration, with the transition concluding after about three years. During the crisis, the extended use of short-time labor subsidies that prevent jobs from being destroyed is likely to have prevented strong increases in unemployment.
Keywords: E24; E32; J64; 330; German Hartz IV reforms; search and matching; unemployment benefits; labor subsidies